Effects of intravenous and oral β-blockade in persistent asthmatics controlled on inhaled corticosteroids. Issue 3 (7th November 2013) - Short, Philip M; Anderson, William J; Williamson, Peter A; Lipworth, Brian J
Abstract : Objective: Despite their benefits in the treatment of cardiovascular disease, β-blockers are seldom used to treat asthmatics. We assessed the safety and tolerability of acute dosing with esmolol and propranolol in patients with asthma. Design: Post-hoc analysis of a double blind, randomised, placebo controlled trial of β-blocker use in asthma. Patients: Mild-to-moderate asthmatics on inhaled corticosteroids. Interventions: Each participant underwent a 6–8 week dose titration of oral propranolol. A subgroup received an intravenous bolus dose of esmolol (0.5 mg/kg). Measurements were recorded pre- and post-esmolol and first dose exposure to 10 mg, 20 mg, and 80 mg of propranolol. Tiotropium was given concurrently with propranolol. Bronchoconstriction was reflected as a fall in forced expiratory volume in 1 s (FEV1 ) or increase in total airway resistance at 5 Hz (R5). Results: 12 patients completed the trial. There were no adverse effects on FEV1 % or R5% following intravenous esmolol. There were significant reductions at 2 min post-esmolol in heart rate (−4.7 beats/min (bpm), 95% CI −7.9 to −1.3 bpm; p=0.002) and systolic blood pressure (−5.9 mm Hg, 95% CI −11.4 to −0.4 mm Hg; p=0.03). No bronchoconstriction was seen during up titration following the first dose of 10 mg, 20 mg or 80 mg of propranolol in the presence of tiotropium. No difference in the asthma control questionnaire at 80 mg propranolol was seen versus placebo in the presence of tiotropium. Conclusions: Intravenous esmolol was administered without any adverse effects on pulmonary function in selected, stable, mild-to-moderate asthmatics controlled on inhaled corticosteroids. Tiotropium prevented propranolol induced bronchoconstriction after acute dosing during up-titration to 80 mg with no adverse impact on asthma control.